Proposta de um plano de gerenciamento de resíduos sólidos domiciliares em acampamentos e aldeias indígenas - Antunes, Ronaldo (2024)
This work highlights the elaboration of a proposal for a Solid Waste Management – ​​PGRS in indigenous villages and camps. The Solid waste management is a growing global challenge as the urbanization and the consumption of industrialized products increase. Given this scenario, it is important to promote in-depth research into waste management household solids. In this sense, the objective of the work is to analyze the types of industrialized foods most consumed in indigenous villages and camps as well such as household waste generated, what is the destination of this waste, and the possible risks to human health and the environment if discarded in an inappropriate location. The search involved data collection through interviews with ten residents in each of the three camps approached in the city of Mato Castelhano/RS using methods of quantitative and qualitative analysis, being classified as exploratory in nature. Furthermore, Disposal practices for the different types of waste generated were evaluated. In the end, through the PDCA and 5’S quality tools, a proposal for implementation of solid waste collection and disposal within villages/camps based on the interpretation of quality tools in continuous improvement.